Industrial Training Report: Perpustakaan Tengku Anis UiTM Kelantan / Mariam Annilla Abdullah - Abdullah, Mariam Annilla (Faculty of Information Management, 2018)
The subject IMC690 Industrial Training is introduced to student for exposed student to real world of professional work specific in workplace chooses. The library I choose (Perpustakaan Tengku Anis) are covered with variety task in real world of library. The unit covered includes Administration units, Customer Services unit, Acquisition unit, Cataloging and Classification unit, Information Technology unit, Information Services unit, Archive unit, Conservation unit and Journal unit. Every unit are exposed with different task and it nature work and every unit have it own responsibility to ensure function of library going smoothly. There are figures and attachment to make this report simply to understand. At the end of report there also have conclusion and recommendation regarding to this industrial training.